THE EFFECT OF AI-PROMPT TEMPLATES ON PRE-SERVICE TEACHERS' ABILITY TO WRITE DOCUMENTARY FILM STORYLINES - Kaewurai, Rujroad; Gumjudpai, Thunyavedee (Journal of Education and Innovation, 2026)
This study aimed to: 1) examine the effect of using the AI-Prompt Template on pre-service teachers' ability to write documentary film storylines; 2) compare the documentary film storyline writing ability of pre-service teachers between an experimental group taught using the AI-Prompt Template and a control group taught using a conventional instruction; and 3) investigate pre-service teachers’ opinions towards the use of the AI-Prompt Template. A quasi-experimental research design was employed. The participants consisted of 54 third-year pre-service teachers enrolled in the Faculty of Education at Naresuan University, who were divided into an experimental group (n = 29) and a control group (n = 25). The research instruments included: (1) AI-Prompt Template for documentary storyline writing developed by the researcher; (2) a documentary storyline writing ability assessment based on a behavioral competency framework; and (3) a questionnaire measuring learners’ opinions toward the use of AI-Prompt Template. Data were analyzed using mean, standard deviation, and independent samples t-test. The results revealed that pre-service teachers who learned through AI-Prompt Template demonstrated significantly higher documentary storyline writing ability than those who learned through conventional instruction at the .05 level. The AI-Prompt Template supported learners in clearly defining main ideas, organizing storyline structures systematically, and logically connecting narrative sequences. In addition, the overall opinions of pre-service teachers toward the use of AI-Prompt Template were at a high level, reflecting positive perceptions of their usefulness in supporting learning and creative and documentary writing. The findings indicate that integrating generative artificial intelligence as a learning support tool can effectively enhance documentary writing competencies among higher education students.